(untitled) (Eurasian Journal of Ecology, 2023)
Data is provided on the general distribution, morphology, phytocenotic preferences of Gagea kamelinii Levichev, and its distinctions from other related taxa in the Platyspermum Boiss section. For the flora of the Kazakh Upland (Ulytauskaia Oblast, Central Kazakhstan), this species is mentioned for the first time. The location represents the northernmost point of its distribution and is associated with chernozem-feathergrass and chernozem-sagebrush (Artemisia terrae-albae Krasch., Krascheninnikovia ceratoides (L.) Gueldst.) communities on light chestnut loamy soils. These findings confirm the natural, historically established distribution of G. kamelinii in the territory of Kazakhstan. The species is typically encountered in populations very rarely and as individual specimens. Morphology throughout ontogenesis and biomorphological features are characterized and illustrated, along with distinctions from closely related species and a section description. Grazing by livestock has been recognized as a limiting factor in the species’ distribution. The inclusion of G. kamelinii in the upcoming edition of the Red Book of Kazakhstan is recommended. The research was conducted using a route-based method and traditional morphological-geographical approaches. Within the territory of Kazakhstan, representatives of the genus Gagea are distributed extremely unevenly. Species diversity sharply increases in mountainous regions, especially in the southern part of the country, and significantly diminishes in the flat lands of Northern and Central Kazakhstan. Key words: Gagea kamelinii, section Platyspermum, distribution, morphological features, ontogeny, rare species, Flora of Kazakhstan.